Media Consumption, Stress and Wellbeing of Video Game and eSports Players in Germany: The eSports Study 2020 - Rudolf, Kevin; Soffner, Markus; Bickmann, Peter; Froböse, Ingo; Tholl, Chuck; Wechsler, Konstantin; Grieben, Christopher (Frontiers in Sports and Active Living, 2022)
The popularity of video gaming and eSports is increasing rapidly. However, most research focusses on the economical features and psychological consequences of gaming and only little is known about the health behavior of the players. Therefore, this study is a follow-up of the eSports Study 2019 and further investigates the health and health behavior of video game and eSports players in Germany. This cross-sectional study, conducted between April and September 2019, includes n=1038 players (91.2% male; 23.0 ± 5.4 years; body mass index: 24.8 ± 5.0 kg/m²) who provided data regarding their health status, physical activity, sleep, media consumption, stress and well-being via a web-based survey. Descriptive statistics were performed on all questions. Linear regressions were used to examine the relation between media consumption, well-being and stress. Almost all respondents classified their health status as “good” or better (92.5 %). The average sedentary and physical activity time was 7.2 ± 3.5 hours/day and 8.8 ± 10.7 hours/week, respectively. Respondents slept for 7.5 ± 1.3 hours/night on weekdays and for 8.5 ± 1.5 hours/night on weekends, but many were “sometimes” or more frequently overtired (53.1 %). Daily duration of playing video games (230.4 ± 159.3 min/day) and watching livestreams and videos with (102.6 ± 101.7 min/day) and without gaming content (72.9 ± 88.5 min/day) were much higher than watching regular television (18.9 ± 49.1 min/day) or reading analogue media (32.1 ± 53.5 min/day). In terms of stress and well-being, most players reported low stress levels (13.8 ± 5.7) and reached a moderate average score of 60.1 ± 16.4 out of 100 points in the WHO-5 Well-Being Index. Linear regressions revealed no relevant significant associations. The results indicate good subjective health and health behavior of the target group. However, the high amounts of screen-based media-consumption, as well as the moderate stress and well-being levels show potential for improvement. In addition, the target group consumed high amounts of digital media in reference to gaming, while traditional media consumption was distinctly low. Consequently, media campaigns that address health promotion in this target group should use the platforms of digital media instead.